Polymorphism of Sex Determination Amongst Wild Populations Suggests its Rapid Turnover Within the Nile Tilapia Species - Triay, Cécile; Courcelle, Maxime; Caminade, Pierre; Bezault, Etienne; Baroiller, Jean-François; Kocher, Thomas D.; D’Cotta, Helena (Frontiers in Genetics, 2022)
Sex-determining regions have been identified in the Nile tilapia on linkage groups (LG) 1, 20 and 23, depending on the domesticated strains used. Sex determining studies on wild populations of this species are scarce. Previous work on two wild populations, from Lake Volta (Ghana) and from Lake Koka (Ethiopia), found the sex-determining region on LG23. These populations have a Y-specific tandem duplication containing two copies of the Anti-Müllerian Hormone amh gene (named amhY and amhΔY). Here, we performed a whole-genome short-reads analysis using male and female pools on a third wild population from Lake Hora (Ethiopia). We found no association of sex with LG23, and no duplication of the amh gene. Furthermore, we found no evidence of sex linkage on LG1 or on any other LGs. Long read whole genome sequencing of a male from each population confirmed the absence of a duplicated region on LG23 in the Lake Hora male. In contrast, long reads established the structure of the Y haplotype in Koka and Kpandu males and the order of the genes in the duplicated region. Phylogenies constructed on the nuclear and mitochondrial genomes, showed a closer relationship between the two Ethiopian populations compared to the Ghanaian population, implying a loss of the LG23Y sex-determination region in Lake Hora males. The genetic basis of sex determination in the Lake Hora population remains unknown.